SOSIALISASI SARAPAN SEHAT PADA MASYARAKAT SEKOLAH DI SDN ANGKE 03 JAKARTA BARAT TAHUN 2016 - Yulia Wahyuni; Prita Dhyani Swamilaksita (Universitas Islam kalimantan MAB, 2016)
Improved nutrition result human resources both physically and mentally healthy.Implementation of improved nutrition is increasing the intake of nutrients according to indidual requirement.Breakfast provides an important contribution to intake total daily nutrition.The results of the survey and research shows that many people who are not breakfast such as student elementary school.Elementary school students is an age group that is still in a growth phase and require nutrients. Treatment of the problems is community service as one Tridarma colleges. The purpose of community service is the school community know the importance of breakfast as well as applying the breakfast every day.Implementation of community service uses puppet show games, reading comics let a healthy breakfast and discourse. Conclusion: Increased of public comprehension Angke 03 elementary schools on healthy breakfast with nutrition education.Keywords: Breakfast, community school, socialization